Design is Everywhere, But Nowhere in Patent Analytics - Taek-Kyun Shin; Jieun Kim (Cubic Journal)
The number of design patents has grown significantly in the last 140 years. However, a data-driven approach for design patents has been overlooked and underutilised in the design management and innovation research communities. Through the prism of a patent professional, data analyst and designer, this photo essay demystifies the complexity of design patent data and sheds light on the underlying value of design as it features among a range of diverse innovation activities. Patent network analysis and visualisation techniques enable the building of a series of patent citation maps and co-inventor networks. Cases from renowned companies—Apple, Dyson, Samsung, and LG electronics— reveal different shapes of innovation activities, focusing on product diversification strategies, collaboration patterns and design-technology cross-pollination flows.